Literature review of information system success models in e-government evaluation - Indra Irmawan; Muh Azis Muslim (Trigin Publisher, 2023)
Evaluation of existing e-government needs to be done so that the existing e-government is following its role in improving government services in terms of effective and efficient public services. The DeLone and Mclean information system success model is a model that can be used to measure the extent to which an information system is implemented, especially e-government. This study aims to determine the evaluation of e-government implementation using the information system success model from DeLone and Mclean, assessing user satisfaction has a significant influence on the use of e-government. This study also analyzes user satisfaction from e-government correlated with the quality of government services in delivering public services. This study uses Systematic Literature Review or SLR. The author conducted a systematic literature review of previous studies published between 2019 and 2022 using a prism reporting mechanism that includes five important steps to take when conducting a systematic review. The results of the study show that evaluating e-government implementation using the information system success model from DeLone and Mclean, the quality of e-government systems significantly influences user satisfaction and the quality of services produced.